Molecular Detection of Fungal Species in a Sample of Iraqi Patients with Meningitis - Ahmed Sahib Abdulamir (Journal of Global Pharma Technology, 2018)
Background: Infections of the central nervous system (CNS) with fungi can cause devastating consequences. Although, several fungi may result in infection of normal humans, most of them are opportunistic and influence immuno-compromised hosts. Invasion of the CNS with fungi can cause one or more the symptoms such as acute or chronic meningitis, abscesses or granuloma encephalitis, stroke, parenchymal brain, or myelopathy. Objective: To assess the frequency of fungal infection as causative agents of meningitis. Patients and methods: Two hundred patients with meningitis, who admitted to three hospitals (name hospitals) in Baghdad, were enrolled in this study from May 2016 to January 2017.The detection methods based on clinical and laboratory criteria and PCR using primers sequence for ITS gene for identification of fungus at species level. Results: The current study showed that, the percentage of aseptic meningitis among immune-compromised patients was 31 samples. The age ranged between (1-78) years. The male to female ratio was 1:1.08. The prevalence of ITS gene was 15.5% detected by PCR, rRNA gene sequencing provides accurate identification information, with the best results obtained of ITS1, ITS4 sequencing. Candida albicans and Cryptococcus neoformans had the highest positive percentage among other species. Conclusion: molecular technique by using PCR is sensitive and accurate tool for diagnosis fungal meningitis. ITS gene is important for detection of fungus in CSF sample. Candida albicans and Cryptococcus neoformans are most commen species caused fungal meningitis.Keywords: Cryptococcus, Candida, Aspergillus, molecular detection of fungal meningitis.